Duplex Reverse Transcription-PCR Followed by Nested PCR Assays for Detection and Identification of Brazilian Alphaviruses and Flaviviruses - Bronzoni, Roberta Vieira de Morais (American Society for Microbiology, 2005)
A new approach was developed for the rapid detection and identification of Brazilian alphaviruses and flaviviruses. The methodology involves the genus-specific detection of Alphavirus and Flavivirus by a duplex reverse transcription-PCR (D-RT-PCR), followed by multiplex nested PCR (M-N-PCR) or nested PCR (N-PCR) assays for species-specific identification. By this protocol, 25 arboviruses were specifically detected and identified. Detection levels between 10(1.3) and 10(3.5) 50% tissue culture infective doses (TCID(50))/ml of Flavivirus and Alphavirus strains were achieved by D-RT-PCR, and levels of <1 TCID(50)/ml were achieved by M-N-PCR assays. To assess the suitability and clinical application of this methodology, a total of 101 human or animal stored samples were analyzed. Results obtained suggest that this technique could be applied as a rapid diagnostic tool in clinical samples in which arbovirus infection is suspected and differential diagnosis is required, avoiding the need to test specimens by separate PCR methods.